Legal basis, standards and criteria for evaluating thermal conditions in forest work - Poje, Anton (Zbornik gozdarstva in lesarstva, 2008)
In this discourse, the Slovene legal basis for thermal conditions at work, together with three international standards for studying thermal conditions SIST EN ISO 7730 (Thermal comfort), SIST EN 27243 (hot environments) and SIST EN ISO 11079 (cold environments), are presented. All three international standards list the criteria for evaluation of thermal conditions and represent the scientific research basis for studying work in practice. For efficient work safety, knowledge of the national legislation is implicit.
Keywords: delovne razmere; delovno okolje; mednarodni standardi; temperatura; zakonodaja